Konsep Pendidikan Seks Pranikah Dalam Kitab Fathul Izar - Suryadi, Ade; Muizzaddin, Najmi; Jamal, Moh. Yusup Saepuloh (Prodi PAI IAILM Suryalaya, 2025)
The nature of humans and animals was created to pair for the sake of progeny. Humans, with their intellect and thinking ability, are responsible for managing this aspect wisely. The essence of marriage is the presence of a child who becomes a qurrota a'yun, a soothsayer, and a valuable treasure for parents. Children are also a field of charity that can pray for parents in the grave. Parents hope that their children will be able to memorize the Qur'an, be filial, and intelligent. However, not all children meet these expectations, despite educational efforts. Many children grow up with morals that are far from spiritual values, so parents' expectations are not met. Based on research, there are various problems that can cause abnormalities in children, one of which is related to the way parents have sex. Islam regulates all aspects of life, including marriage and intercourse, in detail. One solution is to explore the Book of Fathul Izar by K.H Abdullah Fauzi, which discusses marriage with Focus on intercourse, including timing, ordinances, ethics, and related prayers. This research aims to understand the concept and benefits of premarital-sex education in Islam, as well as its explanation in Fathul Izar. The method used is qualitative descriptive, through literature studies, interviews, observations, and documentation. The results of the study show that premarital sex education aims to prepare couples for a harmonious family according to religious teachings. It also includes knowledge of reproductive health and risk avoidance related to sexual activity. This education helps to understand not only sexuality and husband-wife relationships, but also couple psychology. Therefore, it is recommended that adolescents avoid sex outside of marriage and brides-to-be follow premarital sex education guidance. With a good education, future generations are expected to build families that are full of affection and mutual respect.